‘Back to the future’: The ‘new prescriptivism’ in twenty-first-century Britain - Joan C. BEAL (E-REA)
Most introductory textbooks on linguistics make a point of highlighting the distinction between descriptive and prescriptive approaches to the study of language: ‘linguistics is descriptive, not prescriptive” has long been a mantra. Although this is the consensus amongst professional linguists1, prescriptivism is alive and well outside the academy. There is a huge market for prescriptive texts such as Lynn Truss’s Eats, Shoots and Leaves (2003), the best-selling non-fiction book in the UK in the year of its publication. The election of a Conservative-led coalition government in 2010 and a Conservative one in 2015 coincided with a further resurgence of prescriptive attitudes, most infamously in the reaction to a letter signed by 100 academics protesting against the education secretary’s reactionary policies and the introduction of the ‘‘SPaG” (spelling, punctuation and grammar) tests for eleven-year-old pupils. In this paper I examine the phenomenon of popular and institutional prescriptivism in the late twentieth and early twenty-first centuries and consider why, far from receding in the face of descriptive linguistics it is, if anything, resurgent.